NEW LIMITS ON DOMINATING SETS' ENERGY SUM IN PARTICULAR GRAPHS - N. Anbarasi; S. Hemalatha; K. Anitha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The energy sum of a dominating subset of connected & undirected graphs was investigated in this article. A graph Ġ = (X, Y) consists of edges & vertices, which are known as nodes. A subset in a graph's nodes is known as the dominant set Ð; every node in the graph is either within Ð or is adjacent in Ð. The dominating number of network Ġ, abbreviated as γ(Ġ), is the least cardinality for the dominant set. The energy of a simple, connected graph Ġ is calculated by adding its absolute eigen values. The eigen value of a graph's dominating matrix Ð(Ġ) is it's eigen value. In this article, we utilized code for MATLAB and a strategy to investigate the bounds of the energy sum using the dominating matrix.